Effect of pterin impurities on the fluorescence and photochemistry of commercial folic acid - Dantola, Maria Laura (2018)
Folic acid, or pteroyl‑L‑glutamic acid (PteGlu) is a conjugated pterin derivative that is used in dietary supplementation as a source of folates, a group of compounds essential for a variety of physiological functions in humans. Photochemistry of PteGlu is important because folates are not synthesized by mammals, undergo photodegradation and their deficiency is related to many diseases. We have demonstrated that usual commercial PteGlu is unpurified with the unconjugated oxidized pterins 6‑formylpterin (Fop) and 6‑carboxypterin (Cap). These compounds are in such low amounts that a normal chromatographic control would not detect any pterinic contamination. However, the fluorescence of PteGlu solutions is due to the emission of Fop and Cap and the contribution of the PteGlu emission, much lower, is negligible. This is because the fluorescence quantum yield (ΦF) of PteGlu is extremely weak compared to the ΦF of Fop and Cap. Likewise, the PteGlu photodegradation upon UV-A radiation is an oxidation photosensitized by oxidized unconjugated pterins present in the solution, and not a process initiated by the direct absorption of photons by PteGlu. In brief, the fluorescence and photochemical properties of PteGlu solutions, prepared using commercially available solids, are due to their unconjugated pterins impurities and not to PteGlu itself. This fact calls into question many reported studies on fluorescence and photooxidation of this compound.